A taxonomic review of Thiotricha Meyrick, 1886 (Lepidoptera, Gelechiidae, Thiotrichinae) from China, with descriptions of 84 new species - Lee, Ga-Eun; Li, Houhun (Zootaxa, 2024)
Thiotricha Meyrick, 1886 is a large and morphologically diverse genus in the subfamily Thiotrichinae of the family Gelechiidae. The distribution is mainly concentrated in the Old World, but only 14 species were previously known in China. In this study, we reviewed Chinese Thiotricha and examined related species distributed in Korea, Japan, Cambodia and Vietnam. As a result, 84 new species are described in the genus: T. apicispinea sp. nov., T. fasciaria sp. nov., T. atralata sp. nov., T. lativalva sp. nov., T. gracilis sp. nov., T. vittata sp. nov., T. minuta sp. nov., T. albida sp. nov., T. ateriguttata sp. nov., T. parvunca sp. nov., T. eborinicosta sp. nov., T. lacrimiformis sp. nov., T. umbrosidorsa sp. nov., T. asymmetricijuxta sp. nov., T. lunata sp. nov., T. spatulativalva sp. nov., T. uncaticula sp. nov., T. curtisacca sp. nov., T. candidipalpa sp. nov., T. spinesigna sp. nov., T. angusteproducta sp. nov., T. cornuata sp. nov., T. crassiflagella sp. nov., T. minorirugata sp. nov., T. tridentata sp. nov., T. digitiprojecta sp. nov., T. truncata sp. nov., T. peniticoncava sp. nov., T. brevissima sp. nov., T. confluens sp. nov., T. rosatorna sp. nov., T. cochlearis sp. nov., T. albimaculata sp. nov., T. rufimarginata sp. nov., T. deltaloba sp. nov., T. roseapicalis sp. nov., T. jianfengensis sp. nov., T. grandimacula sp. nov., T. latistriata sp. nov., T. contracta sp. nov., T. projecta sp. nov., T. duristria sp. nov., T. robustiseta sp. nov., T. setangulata sp. nov., T. macularis sp. nov., T. vittaticosta sp. nov., T. lineata sp. nov., T. albalata sp. nov., T. disciformis sp. nov., T. rhombiformis sp. nov., T. semota sp. nov., T. karsholti sp. nov., T. wufengensis sp. nov., T. angustifasciata sp. nov., T. anthracina sp. nov., T. longisigna sp. nov., T. cultriformis sp. nov., T. vivida sp. nov., T. magnalata sp. nov., T. rotundata sp. nov., T. guizhouensis sp. nov., T. bicolor sp. nov., T. simplex sp. nov., T. globularis sp. nov., T. xizangensis sp. nov., T. ferruginea sp. nov., T. rosebasis sp. nov., T. nullisigna sp. nov., T. nigrimaculata sp. nov., T. asymmetricosta sp. nov., T. aurea sp. nov., T. lata sp. nov., T. emarginata sp. nov., T. pediformis sp. nov., T. curviciliaris sp. nov., T. recticiliaris sp. nov., T. parvimaculata sp. nov., T. apicidisca sp. nov., T. villosa sp. nov., T. flaviterminata sp. nov., T. hamatisigna sp. nov., T. acicularis sp. nov., T. rosegrammica sp. nov. and T. canimaculata sp. nov. Sixteen species are reported from China for the first time: T. attenuata Omelko, 1993, T. prunifolivora Ueda & Fujiwara, 2005, T. albicephalata Walia & Wadhawan, 2005, T. rhodomicta Meyrick, 1918, T. scioplecta Meyrick, 1918, T. polyaula Meyrick, 1918, T. poecilopa (Meyrick, 1918), T. scatebrosa (Meyrick, 1918), T. clinopeda Meyrick, 1918, T. oxygramma Meyrick, 1918, T. hoplomacha Meyrick, 1908, T. embolarcha Meyrick, 1929, T. hexanesa Meyrick, 1929, T. acrantha Meyrick, 1908, T. scotaea Meyrick, 1908 and T. pyrphora Meyrick, 1918. Four new combinations are proposed: T. barathrota (Meyrick, 1918) comb. nov., T. leucochalca (Meyrick, 1918) comb. nov., T. poecilopa (Meyrick, 1918) comb. nov. and T. scatebrosa (Meyrick, 1918) comb. nov. Based on examination of the type specimens, T. synodonta Meyrick, 1936 is synonymized with T. trichoma. Also, we divide Chinese Thiotricha into four species groups, the subocellea-group, the pontifera-group, the confluens-group and the pancratiastis-group, based on the morphology and the molecular data. Eight species are grouped into another species group (the lata-group) based only on the morphological similarities, but the generic placement of this group needs to be re-evaluated since their morphological traits do not fit well into the generic concept. Fourteen species remain unplaced, and some species such as T. dissobola Meyrick, 1935 and T. pyrphora do not show the typical characteristics of Thiotricha, suggesting that further critical reassessment is also required for the species on the basis of additional morphological and molecular evidence. In this study, a total of 110 species are finally recognized as a result of a taxonomic study on Chinese Thiotricha. Photographs of adults and genitalia are provided for all studied taxa as well as related type specimens deposited in NHMUK and MGBA.